Diagnostics and surgical tactics in the injury of the heart - E. A. Tseimakh; V. A. Bombizo; P. N. Buldakov; N. Yu. Rucheykin; M. E. Tseimakh; V. M. Karkavin; S. A. Dorokhina; A. A. Averkina; D. N. Ustinov (Вестник хирургии имени И.И. Грекова)
The objective is to analyze own clinical observations with the purpose of optimization of diagnostics and application of the adequate medical grant to patients with wounds of heart.Material and methods. The results of treatment of 268 patients with heart wounds operated in the clinic for the last 27 years were analyzed. The majority of patients 202 (75.4 %) had penetrating and through wounds to the heart, 66 (24.6 %) had non-penetrating injuries. The diagnosis was based on clinical symptoms, the results of electrocardiographic, echocardiographic and x-ray studies. The clinical picture depended on the nature of the wound – penetrating or non-penetrating. Videothoracoscopy helped to clarify the nature of the damage of the heart in vague diagnostic cases. In most patients, heart damage was recognized in a timely manner, a diagnostic error was committed in 18 (6.7 %) patients. In 59 (22.0 %) cases, myocardial wounds were stitched with P-shaped sutures, and in 209 (78.0 %) – with nodular sutures.Results. 240 (89.6 %) patients were discharged in satisfactory condition, 11 (4.1%) patients were transferred to the cardiology department for the follow-up treatment, 17 patients died with penetrating or through cardiac injury. The mortality rate was 6.4 %.Conclusion. Emergency surgery is the only effective method of treating heart injury. Long-term results of treatment were traced in 38 patients in terms of 1 year to 10 years. All patients had a clinical recovery.